1074 Is Self-Report following a Motivational Enhancement for CPAP Initiation Group a Predictive Tool for Adherence in a Military Health Setting?. (27th April 2018) - Pham, C K; York, C; Collen, J; Polmear, M; Terry, S
Abstract: Introduction: Perceived readiness, self-efficacy, and social support have been shown to improve CPAP adherence; however, it is unclear how durable the benefits are. Our study aims to determine whether self-reported motivational factors and/or baseline AHI predict CPAP adherence over 6 months following a CPAP initiation class utilizing elements of motivational enhancement in a military health setting. Methods: Observational cohort study at an academic military medical center. We included all military healthcare beneficiaries with OSA who participated in a CPAP initiation class from NOV2016-SEP2017. The class incorporated motivational enhancement techniques within the first 3 weeks of receiving CPAP. Motivational factors (self-rated readiness, self-rated confidence, and social support) and baseline AHI were compared with objectively measured CPAP usage to determine whether these factors could predict CPAP adherence at 1 month, 3 months, and 6 months. Participants that did not provide responses to questionnaire and those without digital adherence data were excluded from analyses. Results: 98 patients (89.8% male, age 44.5 ± 9.1 years) were included in our analysis. The mean AHI was 23.3 ± 19.3 events per hour (47% mild OSA, 24.5% moderate OSA, 28.5% severe OSA). Self-rated readiness displayed a statistically significant correlation with CPAP adherence at all time points evaluated. Self-rated confidence significantly predicted adherence at one-month, but not at 3 and 6 months. Baseline AHI was not associated with CPAP adherence at any time points. Social support significantly predicted CPAP adherence at all time points measured. Conclusion: Self-readiness and social support were predictive of CPAP adherence across all time points measured. Self rated confidence predicted adherence at one month, but not at later time points. Interventions that focus on these measures may improve CPAP adherence for patients with OSA. Consideration for increased frequency of follow up to enhance durability of adherence is suggested by these findings. Support (If Any): No funding sources.